Jewish philosophical polemics against Christianity in the Middle Ages - Lasker, Daniel J. (Littman Library of Jewish Civilization, 2007)
This exposition of the philosophical arguments that Jews have used to refute Christian doctrines makes a major contribution to medieval Jewish intellectual history.